New Tendon Transfer for Correction of Drop-foot in Common Peroneal Nerve Palsy - Vigasio, Adolfo (Springer US, 2008)
Common peroneal nerve palsy has been reported to be the most frequent lower extremity palsy characterized by a supinated equinovarus foot deformity and foot drop. Dynamic tendon transposition represents the gold standard for surgical restoration of dorsiflexion of a permanently paralyzed foot. Between 1998 and 2005, we operated on a selected series of 16 patients with traumatic complete common peroneal nerve palsy. In all cases, we performed a double tendon transfer through the interosseous membrane. The posterior tibialis tendon was transferred to the tibialis anterior rerouted through a new insertion on the third cuneiform and the flexor digitorum longus was transferred to the extensor digitorum longus and extensor hallucis longus tendons. All 16 patients were reviewed at a minimum followup of 24 months (mean, 65 months; range, 24–114 months). The results were assessed using the Stanmore system questionnaire and were classified as excellent in eight, good in five, fair in two, and poor in one. Postoperative static and dynamic baropodometric evaluations also were performed. The proposed procedure, which provides an appropriate direction of pull with adequate length and fixation, is a reliable new method to restore balanced foot dorsiflexion correcting the foot and digit drop and producing a normal gait without the use of orthoses. Level of Evidence: Level IV, therapeutic study. See the Guidelines for Authors for a complete description of levels of evidence. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s11999-008-0249-9) contains supplementary material, which is available to authorized users.